Assessing ICT Awareness and Competency among Commerce Lecturers in Malaysian Polytechnic's: A Preliminary Analysis (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
The Malaysian Higher Education Framework 4.0 is a blueprint produced by the Ministry of Higher Education, Malaysia (MoHE). This framework is referred by higher education institutions to develop their own study programs and comply with international standards and demands. Embedding elements of Information and Communication Technology (ICT) into the curriculum is commonly included in many educational frameworks today. This research conducted to measure the current ICT awareness and competency among commerce lecturers in Malaysian Polytechnic’s. This preliminary research uses descriptive analysis with the mean score formula to classify the level of ICT awareness and competency. The research found that the level of ICT awareness among commerce lecturers was high, with a total mean score of 2.991. The ICT teaching pedagogy also indicated a high level, with a total mean score of 3.209. Additionally, there was a very high level of ICT competency in using web tools and applications, with a total mean score of 3.389. This research finding will contribute as input to the relevant authorities in planning their future plans based on the readiness of commerce lecturers' ICT awareness and competency.